Visual Metaphors of School Expressed Through Caricature - Pavlović, Zlatko M.; Vučetić, Vuk B. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
Understanding the school as an institution and the educational process that takes place within it requires insight into how the school is perceived and experienced, not only by students, teachers, and parents, but also by the broader public. Public perception of school influences the role school plays in the community, how the community relates to it, what it expects from it, and ultimately, how the school functions. Attitudes toward school are expressed in various ways and through different media. One of these is metaphorical: caricature serves as a tool for expressing visual metaphors. This paper presents the results of an analysis of school-related caricatures created by cartoonists from over 30 countries around the world. These caricatures were submitted to an international contest and published in its catalogue. The school metaphors represented in these caricatures were analysed, and the analysis showed that the collected caricatures could be categorized into six distinct groups. These categories can, to some extent, be compared with those identified in other studies that analysed verbal metaphors about school. The general finding is that cartoonists often depict school as a place intended to foster student development, though this goal is frequently not achieved. Some reasons for this include the suppression of students’ individuality, excessive workload, and inappropriate interpersonal relationships, particularly the presence of aggression. The analysis also revealed that caricatures with a critical perspective on school outnumber those with an affirmative tone. However, this disparity in the sample is not large enough to support a definitive conclusion. While cartoonists generally present a critical view of school and its environment, this stance does not apply equally to all aspects of school life. They tend to be considerably more critical of the school as an institution and its surroundings, yet predominantly affirmative regarding the act of learning and the content taught. For cartoonists, the fact that children acquire knowledge at school is viewed positively, whereas the way the institution itself is organized is subject to far greater criticism.
Keywords: metaphors; visual metaphors; school; caricature; school metaphors